Analysis of Facility and Infrastructure Management Based on Practicum Needs at SMK Negeri 1 Pontianak - Munaqib, Munaqib; Radiana, Usman; Ulfah, Maria; Ningsih, Kurnia; Afandi, Afandi (FKIP - Universitas Riau, 2025)
The management of practical facilities and infrastructure is a crucial component of vocational education because it directly affects the quality of learning and students’ readiness to meet industry demands. Many vocational schools still face challenges in planning, maintaining, and optimizing facility use, resulting in practicum activities that do not fully support competency achievement. Strengthening facility management practices that align with industrial standards is therefore essential. This study aims to analyze the management of facilities and infrastructure at SMK Negeri 1 Pontianak based on practicum needs using the POSDCORB theoretical framework. A descriptive qualitative method was employed through in-depth interviews, participatory observations, and documentation studies, supported by source triangulation to ensure data credibility. The findings show that the planning of facility and infrastructure procurement is conducted collaboratively among productive teachers, workshop heads, and industry partners; the organizational structure is clearly implemented through official decrees and SOPs; technical training for teachers and technicians enhances equipment utilization; coordination with internal and external stakeholders is consistently maintained; damage reporting procedures are systematic and well-documented; and budgeting prioritizes essential practicum needs. In conclusion, facility and infrastructure management at SMK Negeri 1 Pontianak demonstrates an adaptive, collaborative, and accountable governance model that effectively supports industry-oriented learning.